Metagenomic Profiles of the Intestinal Virome of Long-Livers - Starikova, Elizaveta V.; Klimina, Ksenia M.; Eudokimova, Anastasia O.; Yeruslanova, Ksenia A.; Gudkov, Denis A.; Gudkov, Denis A.; Kashtanova, Daria A.; Kotovskaya, Yulia V.; Tkacheva, Olga N. (KnE Life Sciences, 2022)
The microbial community of the human intestine is important for maintaining human health. It has been reported that the gut microbiome changes with age, and it can be enrichedwith certain beneficial bacteria while also losing certain commensal bacteria.Little is known about the gut virome of long-livers. Our research aimed to extract, sequence and analyze the viral fraction of long-livers’ gut microbiota in comparison with those of young adults and the elderly. We were thereby able to characterize the gut virome profiles and viral diversity of three age groups. Keywords: aging, gut microbiome, viral metagenomics, bacteriophages